Mechatronic Design, Dynamic Modeling and Results of a Satellite Flight Simulator for Experimental Validation of Satellite Attitude Determination and Control Schemes in 3-Axis - Mendoza-Bárcenas, M.A.; Vicente-Vivas, E.; Rodríguez-Cortés, H. (Journal of applied research and technology, 2014)
This paper describes the integration and implementation of a satellite flight simulator based on an air bearing system, which was designed and instrumented in our laboratory to evaluate and to perform research in the field of Attitude Determination and Control Systems for satellites, using the hardware-in-the-loop technique. The satellite flight simulator considers two main blocks: an instrumented mobile platform and an external computer executing costume-made Matlab® software. The first block is an air bearing system containing an FPGA based on-board computer with capabilities to integrate digital architectures for data acquisition from inertial navigation sensors, control of actuators and communications data handling. The second block is an external personal computer, which runs in parallel Matlab® based algorithms for attitude determination and control. Both blocks are linked by means of radio modems. The paper also presents the analysis of the satellite flight simulator dynamics in order to obtain its movement equation which allows a better understanding of the satellite flight simulator behavior. In addition, the paper shows experimental results about the automated tracking of the satellite flight simulator based a virtual reality model developed in Matlab®. It also depicts two different versions of FPGA based on-board computers developed in-house to integrate embedded and polymorphic digital architectures for spacecrafts applications. Finally, the paper shows successful experimental results for an attitude control test using the satellite flight simulator based on a linear control law. En este artículo se describe la integración e implementación de un simulador de vuelo satelital basado en un sistema de cojinete de aire, el cual fue diseñado e instrumentado en nuestro laboratorio para realizar investigación en el campo de sistemas de control de actitud de satélites, utilizando la técnica hardware-in-the-loop. El simulador de vuelo satelital cuenta con dos bloques principales: una plataforma móvil y una computadora externa donde se ejecuta software desarrollado en Matlab®. El primer bloque, integrado en una plataforma móvil suspendida en aire, contiene una computadora abordo basada en un dispositivo FPGA con capacidad de integrar arquitecturas digitales para adquisición de datos de sensores de navegación inercial, control de actuadores y manejo de datos. El segundo bloque es una computadora personal, donde en paralelo se ejecutan algoritmos basados en funciones desarrolladas en Matlab® para la determinación y el control de actitud. Ambos bloques están unidos inalámbricamente. En este artículo se presenta también el análisis de la dinámica de simulador de vuelo satelital para obtener su ecuación de movimiento, que permite una mejor comprensión del comportamiento del simulador. Además, se muestran los resultados experimentales de seguimiento automatizado del simulador de vuelo satelital basado en un modelo de realidad virtual. Se describe también el desarrollo de dos versiones de computadoras abordo basadas en FPGA para integrar arquitecturas digitales embebidas para aplicaciones en vehículos espaciales. Por último, el artículo muestra resultados experimentales de pruebas de control de actitud utilizando el simulador de vuelo satelital basada en una ley de control lineal.